Совершенствование конструкции профилей для шахтной крепи - Луцкий, М.Б.; Кириченко, В.Я.; Дорожко, И.К.; Чичкан, А.А.; Лигус, Н.Н.; Луценко, В.А. (Геотехнічна механіка, 2004)
Розглянуто існуючі конструктивні особливості профілів для кріплення гірських виробітків. Зроблено аналіз умов їхні роботи, виявлені недоліки. Розроблено новий профіль, у якому за рахунок раціонального розподілу металу підвищені прочностні характеристики як окремих елементів, так і всього профілю. Показано переваги нового профілю перед відомими. Нова конструкція забезпечує фіксацію профілів у вузлах піддатливості, підвищує надійність і безпека роботи. The analysis of the operating conditions of structures in a design mine stull is conducted, their advantages and defects are revealed. To defects of known structures it is possible to relate a not rational cost of metal, absence of reliable fixing of a structure in units of a pliability and low durability of cross section. For removal of the indicated defects the new design is developed and the bill of rating of structures for fastening mountain manufactures. In comparison with known the new structure has increased durability, that allows to reduce a cost of metal, to increase reliability of work of a structure in units of a pliability.